Mobile Learning for Manually Coded Malay Sign Language Using Augmented Reality - Abdul Razak, Raz Nur Izzatu; Senan, Norhalina (Journal of Soft Computing and Data Mining, 2022)
lagging in education as compared to their hearing peers. This can affect their communication skills and affect their academic achievement. However, the existing applications developed for sign language education have a few drawbacks, such as only consisting of a Learning Module, and the media used was only learning videos. Hence, the Mobile Learning for Manually Coded Malay Sign Language using Augmented Reality (KTBM AR) is developed to provide users with Learning and Activity Modules where users can interact with and test their knowledge. Not only that, but KTBM AR also included Augmented Reality (AR) as an interactive learning medium to engage users more in learning. The methodology used in developing this application is the ADDIE model, which comprises five main phases: analysis, design, development, implementation, and evaluation. The result from testing shows that the application was successfully developed with a range of 94% acceptable according to the System Usability Scale (SUS). Thus, it can be concluded that KTBM AR is suitable to be implemented in sign language learning.